2010
DOI: 10.1124/jpet.109.160630
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anticytomegalovirus Activity of Immunosuppressant Mizoribine and Its Synergism with Ganciclovir

Abstract: Cytomegalovirus (CMV) infection is a prominent infection in transplant recipients. The immunosuppressive drug mizoribine was shown to have anti-CMV activity in vitro and was reported to have an anti-CMV effect in renal transplantation. This study characterized the anti-CMV activity of mizoribine in vitro and its synergistic activity with ganciclovir. Mizoribine suppressed replication and at the EC 50 for plaque inhibition of 12.0 g/ml.Mizoribine and ganciclovir exerted a strong synergism in anti-CMV activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…Kuramoto et al . reported MZR as an immunosuppressive and anti‐CMV drug in the clinical regimen was suggested to suppress replication of CMV in vivo and control CMV infection in transplant recipients in combination with ganciclovir . The present results suggest that MZR exerts antiviral activity, and can be considered an advantageous agent for use in combination therapy for CMV infection in renal transplant recipients.…”
Section: Discussionsupporting
confidence: 53%
“…Kuramoto et al . reported MZR as an immunosuppressive and anti‐CMV drug in the clinical regimen was suggested to suppress replication of CMV in vivo and control CMV infection in transplant recipients in combination with ganciclovir . The present results suggest that MZR exerts antiviral activity, and can be considered an advantageous agent for use in combination therapy for CMV infection in renal transplant recipients.…”
Section: Discussionsupporting
confidence: 53%
“…The resultant supernatants were used as the cell-free virus stocks, and their virus titers ranged from 3.3 ϫ 10 3 to 2.3 ϫ 10 5 PFU/ml in this study. The Towne strain of cytomegalovirus (CMV) (18,28) and rhinovirus 13 (13) were propagated in HEL cells, and adenovirus 5 (19) was propagated in Hep2 cells. CMV, rhinovirus 13, and adenovirus 5 were prepared from the infected cells by three cycles of freezing and thawing.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…A report showed that MZR has an effect that directly inhibits CMV plaque formation in vitro, and that MMF exhibits no such effect. The report also indicated a synergistic effect on the anti-CMV activity of MZR when it is used in combination with ganciclovir [23]. MZR, owing to such an effect, may inhibit the reproduction of CMV and exhibit some kind of inhibitory effect on CMV infections.…”
Section: Infectionsmentioning
confidence: 86%